1999
DOI: 10.1023/a:1006118003998
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Two full-length lipoxygenase cDNA sequences (LoxB and LoxC) from barley (Hordeum distichum cv. L. Triumph) are described. The cDNAs share high homology with the barley LoxA cDNA. Southern blotting experiments indicate single copy numbers of the three lipoxygenase genes. RFLP mapping revealed the presence of single lipoxygenase loci. LoxA and LoxB map on chromosome 4 and LoxC on chromosome 7. Two isoenzymes, LOX1 and LOX2, have been purified previously from germinating barley and characterized. LOX1 is encoded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…Two different isoforms, LOX-1 and LOX-2, have been purified and characterised [6]: LOX-1 contributes almost exclusively to the total LOX activity in quiescent grains, whereas LOX-2 activity increases rapidly during germination [7]. Three cDNA sequences encoding the LOX proteins have been isolated from barley grains, and the chromosomal locations of their corresponding genes determined: the LoxA and LoxC clones correspond to the LOX-1 and LOX-2 isoforms, respectively [8], and a third clone, known as LoxB [9], encodes a LOX isoform that has not been identified to date. The LoxA and LoxB loci are tightly linked (1 cM) and map to chromosome 4HS, whereas LoxC maps to the long arm of chromosome 5H [9].…”
Section: Introductionmentioning
confidence: 99%
“…Two different isoforms, LOX-1 and LOX-2, have been purified and characterised [6]: LOX-1 contributes almost exclusively to the total LOX activity in quiescent grains, whereas LOX-2 activity increases rapidly during germination [7]. Three cDNA sequences encoding the LOX proteins have been isolated from barley grains, and the chromosomal locations of their corresponding genes determined: the LoxA and LoxC clones correspond to the LOX-1 and LOX-2 isoforms, respectively [8], and a third clone, known as LoxB [9], encodes a LOX isoform that has not been identified to date. The LoxA and LoxB loci are tightly linked (1 cM) and map to chromosome 4HS, whereas LoxC maps to the long arm of chromosome 5H [9].…”
Section: Introductionmentioning
confidence: 99%
“…Segregation analysis revealed that LOX thermostability types in the Steptoe/Morex DHLs were governed by a single locus, located at the same locus as the LOX-1 structural gene of chromosome 4H. It is clear that the factor controlling LOX thermostability types was located at the LoxA locus which corresponds with the LOX-1 structural gene [4]. To understand the diversity in the thermostability of seed lipoxygenase-1 (LOX-1), Hirota et al .…”
Section: Discussionmentioning
confidence: 99%
“…LOX-1 is encoded by LoxA mapped on chromosome 4H, while LOX-2 is encoded by LoxC on chromosome 5H [3]. Expression of a third LOX isoform encoded by LoxB, and similar to that of LOX-2, has been detected only after germination and the causal gene has not been identified [4]. …”
Section: Introductionmentioning
confidence: 99%
“…For example, three Lox genes were identified in barley— Lox - 1 ( LoxA ), Lox - 2 ( LoxC ), and Lox - 3 ( LoxB ) (Rouster et al 1997, 1998; van Mechelen et al 1999; van Mechelen et al 1995). In beer production, LOX-1 catalyzes the formation of 9-HPOD while LOX-2 catalyzes the formation of 13-HPOD.…”
Section: Introductionmentioning
confidence: 99%
“…In beer production, LOX-1 catalyzes the formation of 9-HPOD while LOX-2 catalyzes the formation of 13-HPOD. LOX-3 is considered irrelevant to beer quality given its low expression level in barley kernels and unclear product specificity (van Mechelen et al 1999). Collectively, LOX-1 is considered the main contributor to malt LOX activity (Doderer et al 1992; Kuroda et al 2003; Yang and Schwarz 1995).…”
Section: Introductionmentioning
confidence: 99%